CITRA WANITA DI DALAM VEDA - I Gusti Agung Istri Agung (UHN IGB Sugriwa Denpasar, 2022)
The image of a Hindu woman who is eye-catching, superior, benevolent, luminous, the image of a woman can be seen in many colors, noble, radiant, clear, beautiful, pleasing to the eye as an image, likeness, figure. Physically, the ideal woman is coveted by every human being. In Hinduism which is applied in the teachings of the Vedas, women who have purity, women who are wise and women who have knowledge. In the Vedas a woman also has the virtue of being a woman, that is, traits that should be cultivated are pioneers, brilliant. support (lighten the husband/parents' duties), give or serve food, carry out dhanna as motherland. A woman is required to practice modesty (when walking and sitting), intelligent (able to become a scholar) and as a teacher (guidance), in the past (and today) participating in going and fighting on the battlefield, being brave, articulate and confident.